Advancing sports medicine through technology: some applications and future visions - Amirouche, Farid; Patel, Ishani (Frontiers in Musculoskeletal Disorders, 2025)
IntroductionThis paper examines the transformative impact of technology on sports medicine, highlighting its current applications and prospects. As advancements continue to emerge, the integration of innovative tools aims to enhance athlete care and improve performance.Hypothesis and aimThe study's primary objective is to evaluate the effectiveness of diagnostic imaging, wearable devices, motion capture systems, and data analytics in the prevention, diagnosis, and rehabilitation of athletic injuries. Furthermore, it aims to highlight the potential of current sports data collection methods to advance preventive medicine and to leverage virtual simulations to assess injuries and optimize rehabilitation practices.MethodologyA comprehensive analysis of recent technological advancements in monitoring and data collection is conducted, focusing on their role in preventing injuries related to overuse and fatigue. By leveraging real-time data, these technologies enhance athlete performance and safety.ConclusionBy highlighting these technological advancements, this study articulates a visionary perspective on the future of sports medicine. It demonstrates how the effective integration of athlete data can elevate treatment protocols, refine prevention strategies, and ultimately enhance athletes' outcomes. The paper also discusses key innovations across biomechanics, wearable technology, advanced diagnostic imaging, rehabilitation technologies, machine learning, and immersive training experiences, underscoring the critical intersection of engineering and sports medicine.